Newspaper as source of history: A case study of daily “Zamindar” of Maulana Zafar Ali Khan - Suleman, Zahida (2014)
Historians generally use newspaper for three purposes: Learning facts about specific events  Looking for long term trends  Searching for details or the texture surrounding an event – a fact or story that illuminates or complicates a larger pattern.It means that newspapers are very important source for writing history. It fills the gaps between historical, social, political events which are ignored by other sources.After the War of Independence (1857), Muslims were continuously being suffered socially, economically and politically by the ruler.In these circumstances Sir Syed Ahmad khan (1817-1898) started his movement for reforming the Muslim society. He decided to use the power of the press to communicate his message to the Muslims of India. He not only preached the loyalty to the British but his journalism was also aimed at the social reforms.Sir Syed formed a society called the scientific society in 1863 and it brought out a paper, the Scientific Society Magazine. It aimed at disseminating correct, accurate and authentic news of national and international significance. The paper was absolutely free from exaggeration.3In1870, he started Risala-Tahzib-Ul-Akhlaq Both the newspapers proved themselves a source of history at that time.Twentieth century is known for the political development and awareness of the Muslims of India The Muslims established a political partyin 1906 in the name of All India Muslim League and the Muslim leadership started trying to protect the rights of Muslims of India. Muslim press also played its role for their political consciousness. With the start of the second decade of the century, the Muslims created new and young journalists which were anti British and with the vengeance. Muhammad Ali Jauhar started his ‘Comrade’ followed soon after by the Urdu paper ‘Hamdard’. MaulanaAbulKalam Azad embarked on his adventure periodical journalism in the shape of ‘Al – Hilal’ andZafar Ali Khan converted the ‘Zamindar’ to an Urdu daily from Lahore.This research paper is about the contribution of daily “Zamindar” which proved itself a source of history whether those were the internal political issues of India or out of India. Like, the British attitude towards Turkey during First World War and the ensuing of the Khilafat issue, which was completely reported by the newspaper. It also contributed equally in pan Islamism, Hindu – Muslim unity, women and student participation in the politics for the first time.Zamindar also contributed its role for the constitutional development in Muslim Populated areas like NWFP(North West Frontier Province) and Baluchistan. It also played significant role in the reorganization of the Muslim League and to promote the idea of a separate homeland for the Muslims of South Asia. So, Zamindar proved itself a source of history from the First World War to the end of Second World War and for a demand of separate country for the Muslims of India (Pakistan).However no independent book or article has been written about the role of ‘Zamindar” for those issues and the area remained largely neglected.This research paper focuses on the material presented in the “Zamindar” and by an indepth analysis of its contents, along with other primary and secondary sources, attempts to highlight its role in bringing about that newspaper is an important source of history. It argues that “Zamindar” through its news, editorials and articles played a significant role in the political awakening of the Muslims of India and proved itself a source of history for the Muslims of South Asia.